Innovative development of small and medium businesses in the conditions of war and post-war recovery - IVANOVA, Tetiana (Ways to Improve Construction Efficiency, 2025)
The article examines the role and contribution of small and medium-sized businesses to the country's economic development during the war and reconstruction. It is argued that the full-scale war significantly transformed the nature of business activity, strengthening the role of flexible management solutions, digital technologies and organizational innovations as key factors for the survival and growth of business entities. Despite significant destruction and logistical challenges, the small and medium-sized business sector demonstrated a high level of adaptability, often implementing survival innovations, in particular, in the areas of relocation, reorientation of supply chains and digitalization of operational activities. It is determined that digital transformation has become a critically important factor in supporting the continuity of business processes, ensuring the transition to remote work formats and the development of new sales markets. The main barriers to the implementation of innovations in SMEs are analyzed, among which the shortage of financial resources, destruction of production infrastructure, limited access to sales markets, personnel losses and increased risks of doing business are highlighted. The study emphasizes the role of state support and international assistance in stimulating the innovative activity of enterprises, in particular through grant funding programs, tax incentives, preferential lending and the development of innovation infrastructure institutions. The post-war recovery of the Ukrainian economy will be accompanied by a structural transformation of SMEs in the direction of increasing intellectual capital, technological component, development of creative industries, innovative economy and digital services. The need to systematize models of innovative development of SMEs in crisis conditions and the formation of practical recommendations for ensuring their competitiveness in the short and long term is substantiated. The article emphasizes the possibility of their use in the process of developing regional programs to support entrepreneurship and strategies for post-war economic recovery.